Vibrio harveyi effect under survival of Litopenaeus vannamei larvae - Aguirre-Guzmán, Gabriel (2013)
The culture of aquatic organisms show a high relevance in the human feeding and the culture activities can create artificial conditions that increase the growth and selection of specific bacteria. Vibrio species are normal bacteria’s from microflora of penaeid shrimp, those are opportunistic pathogens that can take advantage of the ecological changes generated for the culture of aquatic organisms and which may cause diseases, low survival and economic losses in the shrimp production. The aim of this research was to determine the variation in the survival of different larval substages (nauplius, zoea I-III, mysis I-III) and postlarvae 1, of Pacific white shrimp Litopenaeus vannamei exposed at three doses [103 , 105 , and 107 colony-forming unit (CFU) ml-1 [ of V. harveyi, by immersion (30 min) as infection method. This species generated a significant low survival in larvae (p < 0.05) only in high doses (105 and 107 CFU ml-1 ), where higher doses show the lowest values of survival. Larval substages and postlarvae 1 of shrimp showed sensitivity associate to the increase of Vibrio doses and this sensitivity decreased with the growth of larval substages and postlarvae 1. This information has high significance for the fisheries and aquaculture industry, which help to generate strategies to reduce the effects of V. harveyi with positive effect in growth and survival of the shrimp larvae and postlarvae 1.